2006
DOI: 10.1152/physiolgenomics.00314.2005
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome, transcriptome, and bioinformatic cis-element analyses point to HNF-4 as a central regulator of gene expression during enterocyte differentiation

Abstract: DNA-binding transcription factors bind to promoters that carry their binding sites. Transcription factors therefore function as nodes in gene regulatory networks. In the present work we used a bioinformatic approach to search for transcription factors that might function as nodes in gene regulatory networks during the differentiation of the small intestinal epithelial cell. In addition we have searched for connections between transcription factors and the villus metabolome. Transcriptome data were generated fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
99
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 48 publications
9
99
0
1
Order By: Relevance
“…Conditional knockout of HNF-4␣ demonstrated its crucial role into the embryonic development of the mouse colonic epithelium, but its role in the small intestinal context still remains to be investigated (14). Metabolome, transcriptome, and bioinformatic analyses indicated that HNF-4␣ could be implicated in intestinal lipid metabolism with the regulation of apolipoprotein synthesis (53). Our findings demonstrate that HNF-4␣ is a potent activator of several intestinal genes normally associated with mature enterocyte functions.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…Conditional knockout of HNF-4␣ demonstrated its crucial role into the embryonic development of the mouse colonic epithelium, but its role in the small intestinal context still remains to be investigated (14). Metabolome, transcriptome, and bioinformatic analyses indicated that HNF-4␣ could be implicated in intestinal lipid metabolism with the regulation of apolipoprotein synthesis (53). Our findings demonstrate that HNF-4␣ is a potent activator of several intestinal genes normally associated with mature enterocyte functions.…”
Section: Discussionmentioning
confidence: 71%
“…HNF-4␣ is considered to be the master regulator of the human hepatocyte where it controls the expression of molecules implicated in lipid uptake and transport (20,28,36,61). HNF-4␣ is expressed along both the vertical and horizontal axis of the gut epithelium and regulates intestinal epithelial expression of alkaline phosphatase, ApoA-IV, and meprin-1␣ genes (37,49,53). Conditional knockout of HNF-4␣ demonstrated its crucial role into the embryonic development of the mouse colonic epithelium, but its role in the small intestinal context still remains to be investigated (14).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of the pathways identified to date include the Wnt pathway (2), the Notch pathway (3), the Hedgehog system (4), members of the transforming growth factor-␤ family including the bone morphogenetic proteins (5), and the phosphatidylinositol 3-kinase pathway (6). The intestine specific gene expression requires the tightly regulated activity of transcription factors, including the well characterized key factors HNF1␣/␤, 2 HNF4␣, GATA factors, ETS, CDX1, and CDX2 (7)(8)(9)(10)(11)(12)(13). These transcription factors often cooperate to control the expression of the intestinal specific genes; until now, in particular HNF1␣, GATA4 -6, and CDX2 have been found to interact in order to regulate the activity of several promoters in the intestine (7, 14 -20).…”
mentioning
confidence: 99%